(untitled) (Journal of Economics and Management Research, 2020)
نحاول من خلال هذه الدراسة التطرق إلى موضوع اصلاح بيئة أداء الأعمال التي تدعم الأداء التنافسي في الجزائر مقارنة مع الدول العربية الأخرى والتي قطعت أشواطا في مسار التنمية الشاملة، ولكنها في سلم المؤشرات صنفت في المراتب الأخيرة عالميا خاصة ضمن بيئة الأعمال الحالية والبيئة التنافسية، ومن خلال تحليل مؤشراتها خلال الفترة الزمنية (2017-1986) ومختلف الاستراتيجيات والإصلاحات المعتمدة لرفع مستويات الاقتصاد الوطني لكل دولة، تبين ان اغلب اقتصاديات الدول العربية وخاصة الجزائر لابد أن تعمل جاهدة لمحاربة الفساد وتعزيز الشفافية وتثبيت الإصلاحات الاقتصادية والمؤسساتية كأفضل السبل لمواجهة التحديات الحالية في ظل بيئة الاعمال وتنافسية الاقتصاد الحالي. In this article we try to address the issue of reforming the business performance environment that supports the competitive performance in Algeria compared to other Arab countries, which have made strides in the path of comprehensive development, but in the index ranks in the last ranks globally, especially within the current business environment and competitive environment, and through analysis Indicators during the period (1986-1998) so it must work hard to fight corruption and enhance transparency and stabilize economic and institutional reforms as the best ways to meet the current challenges in an environment Business and the current competitive economy. Keywords: business environment in Arab countries, corruption, institutional performance indicators in Algeria.